Pendampingan Belajar Siswa Sekolah Dasar di Era New Normal - Asrul Nazar; Fika Ibrahim; Sandita S Naim (Society : Jurnal Pengabdian Masyarakat, 2022)
The purpose of this service is to overcome problems and help the community, especially elementary school students who experience obstacles in learning activities at home because learning is done online, help lower class students who do not have access to teaching materials at home, Help borrow learning facilities and media at home, Help ease the burden on parents in educating their children at home. With this service, parents can use gadgets for their children's online learning during the COVID-19 pandemic, elementary school students are helped in providing teaching materials, loan facilities, and learning media, and parents are greatly helped by this service. mentoring activities during the COVID-19 pandemic and in studying at home during the COVID-19 pandemic while still paying attention to health protocols.